ANALYSIS OF THE ROLE OF EDUCATION IN DRIVING TECHNOLOGICAL INNOVATION IN THE BUSINESS WORLD - Sutrisno, Sutrisno; Hadi, Dwi Prasetiyo; Wibowo, Bagus Yunianto; Prayitno (Technopreneurship and Educational Development Review (TENDER), 2024)
Education plays a crucial role in shaping individuals' ability to innovate. A robust and relevant education system will produce human resources capable of adopting, developing, and implementing new technologies. However, it is important to understand the extent to which education influences technological innovation in the business world. This research aims to delve deeper into the role of education in driving innovation and to identify effective strategies to enhance education's contribution in addressing challenges and leveraging opportunities in the era of technological innovation. This research method will adopt a qualitative literature review approach focusing on the analysis and synthesis of relevant literature from the period of 1999-2023. The study results indicate that the role of education in driving technological innovation in the business world is highly significant. Education not only shapes individuals with the knowledge and skills needed to develop new technologies but also cultivates an innovative mindset and a collaborative culture essential in the innovation process. Educational institutions also serve as a platform for the exchange of ideas and knowledge among various stakeholders, as well as facilitators in expanding access to resources and opportunities for individuals from diverse backgrounds.